Principles of organizational behaviour - Fincham, Robin (Oxford University Press, 2005)
Written jointly from psychological and sociologicalperspectives, this text covers the range of disciplines across occupationalpsychology, group dynamics, and work and organizations. The new edition hassubstantially revised, updated and newly formatted, and includes a wide range ofadditional material